Effects of Tert-Butylhydroquinone on Intestinal Inflammatory Response and Apoptosis following Traumatic Brain Injury in Mice. (28th December 2010) - Jin, Wei; Ni, Hongbin; Dai, Yuxiang; Wang, Handong; Lu, Tianyu; Wu, Jun; Jiang, Jian; Liang, Weibang
Abstract : Traumatic brain injury (TBI) can induce intestinal inflammatory response and mucosal injury. Antioxidant transcription factor nuclear factor erythroid 2-related factor 2 (Nrf2) has been shown in our previous studies to prevent oxidative stress and inflammatory response in gut after TBI. The objective of this study was to test whether tert-butylhydroquinone (tBHQ), an Nrf2 inducer, can protect against TBI-induced intestinal inflammatory response and mucosal injury in mice. Adult male ICR mice were randomly divided into three groups: (1) sham + vehicle group, (2) TBI + vehicle group, and (3) TBI + tBHQ group (n = 12 per group). Closed head injury was adopted using Hall's weight-dropping method. Intestinal mucosa apoptosis and inflammatory-related factors, such as nuclear factor kappa B (NF- κ B), tumor necrosis factor- α (TNF- α ), interleukin-1 β (IL-1 β ), interleukin-6 (IL-6) and intercellular adhesion molecule-1 (ICAM-1), were investigated at 24 h after TBI. As a result, we found that oral treatment with 1% tBHQ prior to TBI for one week markedly decreased NF- κ B activation, inflammatory cytokines production, and ICAM-1 expression in the gut. Administration of tBHQ also significantly attenuated TBI-induced intestinal mucosal apoptosis. The results of the present study suggest that tBHQ administration could suppress the intestinal inflammation and reduce the mucosal damage following TBI.